Tunneling in the Hydrogen-Transfer Reaction from a Vitamin E Analog to an Inclusion Complex of 2,2-Diphenyl-1-picrylhydrazyl Radical with β-Cyclodextrin in an Aqueous Buffer Solution at Ambient Temperature - Ikuo Nakanishi; Yoshimi Shoji; Kei Ohkubo; Shunichi Fukuzumi (MDPI AG, 2021)
Recently, increasing attention has been paid to quantum mechanical behavior in biology. In this study, we investigated the involvement of quantum mechanical tunneling in the hydrogen-transfer reaction from Trolox, a water-soluble analog of vitamin E (α-tocopherol), to 2,2-diphenyl-1-picrylhydrazyl radical (DPPH•) in a phosphate buffer solution (0.05 M, pH 7.0). DPPH• was used as a reactivity model of reactive oxygen species and solubilized in water using β-cyclodextrin (β-CD). The second-order rate constants, kH and kD, in 0.05 M phosphate buffer solutions prepared with H2O (pH 7.0) and D2O (pD 7.0), respectively, were determined for the reaction between Trolox and DPPH•, using a stopped-flow technique at various temperatures (283-303 K). Large kinetic isotope effects (KIE, kH/kD) were observed for the hydrogen-transfer reaction from Trolox to the β-CD-solubilized DPPH• in the whole temperature range. The isotopic ratio of the Arrhenius prefactor (AH/AD = 0.003), as well as the isotopic difference in the activation energies (19 kJ mol−1), indicated that quantum mechanical tunneling plays a role in the reaction.